Endogenous Fluorescence Analysis: Preliminary Study Revealing the Potential of this Non‐invasive Method to Study Mummified Samples. (3rd May 2017) - Zanello, M.; Pallud, J.; Jacqueline, S.; Augias, A.; Varlet, P.; Devaux, B.; Nielsen, O.; Abi Haidar, D.; Charlier, P.
Abstract: Autofluorescence analysis allows new insights on human tissue without any dye in a non‐invasive way and therefore seems well suited to study historical samples. An optical set‐up recorded emitted autofluorescence in 1/spectral and 2/lifetime domains from different samples' regions of interest. The studied samples were a mummified right hand, bog body (Tollund Man) feet and a male Caucasian hand (control sample). Spectral analysis revealed that mummified hand exhibited broad autofluorescence spectra, whereas Tollund Man's feet exhibited a weak single peak with 405‐nm excitation wavelength. Control sample spectra are weaker than that of the mummified hand but higher than the Tollund Man's feet. Lifetime measurements indicated the presence of classical endogenous fluorophores on the mummified right hand. The Tollund Man's feet exhibited two patterns of lifetime measurements: healthy zone exhibited lifetime values at four emission wavelengths but skin lesions at only two wavelengths. This first report of mummified samples' autofluorescence analysis suggests the potential of optical analysis for archeologic research. Copyright © 2017 John Wiley & Sons, Ltd.